Characterization of locally extracted red and green clay and study of its effect against toxicity and oxidative stress caused by lead in rats - Kenioua Achouak; Ben aoun Khadidja (University of Eloued جامعة الوادي, 2021)
The objective of this work is to study the effects of red and green Clay on changes in biochemical, haematological, oxidative stress and histopathological parameters in rats acutely exposed to lead acetate. The experimental study carried out in the laboratory on 25 male Wistar rats which divided into five group of five rats in each, the first group served as control, the second group is contaminated with lead, the third group is contaminated with lead and treated with red clay, the fourth group is contaminated with lead and treated with green clay. Some biochemical, haematological, oxidative stress parameters were analysis. From the analysis of our results, we observe a considerable change in body weight and an increase in the relative weight of liver, kidney and heart in rats contaminated with lead compared to control. The results also showed notable changes in the biochemical parameters, by a decrease in the serum glucose concentration (P˃0.05), uric acid calcium level, iron (p <0.001) and serum creatinine concentration (p˂0.01). While urea was significantly increased. However, serum transaminase enzymes (TGP, TGO) activities were increased in rats contaminated with lead in comparison with control. The results obtained revealed also a haematological toxicity and oxidative stress in rats contaminated with lead and a decrease in Hb, HCT, MCV, WBC levels and in tissular GSH concentration and an increase in PLT, RBC, granulocytes, tissular MDA, GST and SOD levels compared to control. Also, the results clearly showed alterations in the structures of the tissues studied in comparison with the controls, with hemorrhage, inflammation with hepatic and testis necrosis. Treatment with red and green clay partially ameliorates biochemical, hematological and oxidative stress parameters, with protection and regeneration of the tissue against free radical attacks caused by lead. In conclusion, this study shows that treatment with red and green clay induces a beneficial effect against lead toxicity at molecular and tissue level
Applied Biochemistry
Keywords: Lead; toxicity; clay; oxidative stress; Wistar rats